Qualitative Study of Amino Acids in Red-rot Disease Infected Sugarcane Using FT-NMR Spectral Study - Raja Kumar, N.; Narayanaswamy, R. (Asian Journal of Chemistry, 2016)
An attempt has been made to determine the variation of intensity in amino groups of resistant and red-rot disease infected sugarcane crop using 1H NMR spectral study. From this study it has been shown that the FT-NMR can be used as a rapid confirmatory method for the qualitative analysis of amino acids present in resistant and red-rot disease infected sugarcane crop.